The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1111/hae.13640
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a standardized protocol for thrombin generation using the calibrated automated thrombogram: A Nordic study

Abstract: Introduction The thrombin generation assay‐calibrated automated thrombogram (TGA‐CAT) method is used to measure the overall coagulation capacity in plasma. However, the method is still considered to be a research tool, mainly because of its’ lack of standardization. Aim Our study aimed to further raise the standardization level for the TGA‐CAT method by evaluating a detailed standardization protocol and three reference plasmas’ (RP)s ability to normalize results. Methods Six Nordic centres participated in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…Finally, the number of non‐responders in the TGA‐CAT measurement was unexpectedly high, which may reflect TFPI activity or fibrin abnormality during the early state of critical illness. However, our laboratory has fulfilled the new standards for TGA‐CAT measurement with a coefficient of variation of 10%‐14% 37 . Thus, we suggest that preanalytical properties (eg, shade of plasma during pancreatitis) may limit the use of the TGA‐CAT method in critically ill patients, as previously reported 38 …”
Section: Discussionmentioning
confidence: 57%
“…Finally, the number of non‐responders in the TGA‐CAT measurement was unexpectedly high, which may reflect TFPI activity or fibrin abnormality during the early state of critical illness. However, our laboratory has fulfilled the new standards for TGA‐CAT measurement with a coefficient of variation of 10%‐14% 37 . Thus, we suggest that preanalytical properties (eg, shade of plasma during pancreatitis) may limit the use of the TGA‐CAT method in critically ill patients, as previously reported 38 …”
Section: Discussionmentioning
confidence: 57%
“…25,38,39,40 The thrombin generation assay has not been universally accepted as a biomarker in clinical settings 41,42 however, a recent thrombin generation standardization study showed that the standard thrombin generation assay provides good reproducibility in hypercoagulable plasma. 43 When D-dimer and ETP are combined with the Thrombogyn score, the predictive ability of the Thrombogyn score was enhanced.…”
Section: Discussionmentioning
confidence: 99%
“…The thrombin-generation assay is not routinely available; however, a recent study has shown that, when normalized, the thrombin-generation assay has similar reproducibility to many standard coagulation assays used in the clinic. 43 Near-patient testing has been described for the thrombin-generation assay; hence, it has the potential to become a more accessible assay in the future. 44 Due to the lack of available plasma, we did not include the biomarkers in the original derivation model, and our biomarkers were selected based on previous evidence.…”
Section: Limitationsmentioning
confidence: 99%
“…TG-experiments are known for almost a century but became available for clinical- and pharmacological use with the advent of a semi-automated method (13, 14). The practical applicability has been delayed by problems of inter-laboratory repeatability but lately it has been shown that the experimental error is not worse than that of other coagulation-related tests (15, 16). For routine use different types of laboratory automatons have become available (17), but they are not yet in general use.…”
Section: Thrombin Generation Capacity Predicts Thrombotic and Bleedinmentioning
confidence: 99%
“…In view of the large interindividual differences in heparin responsiveness heparin dosage should be personalized so as to obtain an ETP of around 50% of the average in the normal normal population, i.e., 600–700 nM min (16). We hope that this paper might lead to rounding up experts in the field in order to start and perform a collaborative study that proves the suitability of ETP for this purpose.…”
Section: The Ideal Heparin Dosingmentioning
confidence: 99%